Impact of Telephone Follow-Up on Patient Satisfaction in a Pediatric Neurosurgery Clinic. (December 2020) - Blanco, Erica; Samuels, Shenae; Kimball, Rebekah; Patel, Daxa; Citty, Sandra; Spader, Heather
Patient satisfaction is a key metric used to measure quality in health care. However, patient satisfaction measures in the pediatric population are less studied and understood than in the adult population. The purpose of this study was to evaluate the impact of telephone follow-up on patient satisfaction in an outpatient pediatric neurosurgery clinic. A standardized telephone follow-up call was performed within 1 week of a child's clinic visit. Pearson's χ 2 or Fisher's exact tests were used to assess changes in patient satisfaction measures after implementation of the telephone follow-up call initiative. The proportion of overall "top-box" physician rating significantly increased from 85.5% in 2017 to 95.6% in 2018 ( P = .04). There was also a nonsignificant upward trend in the proportion of respondents noting that they would recommend this provider, as well as in all measures of physician communication quality and office staff quality. A simple telephone call to new patients after an outpatient pediatric neurosurgery clinic visit resulted in statistically significant and clinically meaningful changes in patient satisfaction scores.